Analysis of Food Cost and Food Perception with Food Waste of The Supplemental Food for School Children in Elementary School Children at Kulon Progo District - Andi Yuniarsy Hartika; BJ Istiti Kandarina; Nur Hadi Ihwani (Darussalam Nutrition Journal, 2023)
Background: The success of the Supplemental Food for School Children program is determined  by the child's acceptance of the food provide. Objective: to analyze appropriate costs and perceptions of food with additional food leftovers for elementary school children in Kulon Progo Regency. Methods: The research design is a cross-sectional design. This research was conducted on 89 elementary school children from grade IV to grade VI in 4 elementary schools that received PMT AS in Kulon Progo District with simple random. The research instrument used a food cost calculation form, a food perception questionnaire with a smiley face, a food weighing device, a comstock scale form with a 6-point visual estimation method. Analysis of bivariate using chi square test and multivariate using logistic regression test.Results: The bivariate analysis results showed a significant relationship between the cost of food and the perception of The Supplemental Food for School Children with p = 0.002. There is a significant relationship between food perception and food waste of The Supplemental Food for School Children with p = 0.000. Finally, there is a significant relationship between food costs and food waste with p = 0.007. The results of multivariate analysis, food costs and perceptions contributed 29% to reducing food waste. Conclusion: Appropriate food costs and perceptions of preferred the food are associated with the least leftover food waste for school children. Key words : Food Cost, Food Perception, Food Waste